Agricultural strategy development in West Africa: The false promise of participation? - Resnick, Danielle; Birner, Regina (International Food Policy Research Institute, 2008)
Participatory approaches are an increasingly prominent technique for designing agricultural strategies within Sub-Saharan Africa. However, such approaches are frequently criticized for either not involving enough stakeholders or limiting the scope of their participation. By analyzing the role of stakeholder participation in the formulation of agricultural and rural development strategies in West Africa, this paper finds that a lack of broad-based participation in these strategies was not a major problem. Rather, the real challenge lies in transforming the outcomes of participatory processes into policies that can be feasibly implemented. The paper highlights why an emphasis on participatory processes can sometimes result in disappointment among stakeholders and discusses a range of measures to help overcome this dilemma.